Shell shocked roducer/director, Terry Messenger - Messenger, Terry; BBC worldwide (North Sydney, NSW : BBC Worldwide, 2004)
Royal Dutch/Shell was seen as the safest of havens for money invested by insurance companies and pension funds. If you needed a safe, steady return on your money, you could, as the slogan declares, always'be sure of Shell'. But on 9th January 2004, the oil giant stunned the financial world by confessing to a 20% exaggeration of its proven oil reserves. Shell's share price crashed and 3 billion pounds was wiped off the value of people's investments. How did this gross over-exaggeration happen?
Title from title screen
DVD format
Keywords: Petroleum industry and trade